A signal on-off ratiometric electrochemical sensing platform coupled with a molecularly imprinted polymer and CuCo2O4/NCNTs signal amplification for selective determination of gemcitabine - Hatamluyi, Behnaz; Sadeghzadeh, Samira; Sadeghian, Reihaneh; Mirimoghaddam, Mohammad Mobin; Boroushaki, Mohammad Taher (Sensors and actuators. B, Chemical, 2022)
A novel and reliable electrochemical analysis tool was developed for gemcitabine (GEM) detection by combining the selective recognition of molecular imprinted polymer (MIP) technology and ratiometric quantification strategy. In this contribution, a glassy carbon electrode (GCE) surface was first modified by drop-coating CuCo2O4/NCNTs and ferrocene (FC) to achieve a ratiometric on-off response (CuCo2O4/NCNTs/FC was served as a substrate to amplify signal and to provide reference signal). Then, MIP network was prepared through in situ electrochemical polymerization, using aniline as monomer and GEM as template. Differential pulse voltammetry (DPV) analysis showed that the oxidation peak signal of FC decreased with the increase of GEM concentration, whereas the oxidation peak signal of GEM increased. Therefore, the peak current ratio of IGEM/IFC was employed to accurately reflect the concentration of GEM. Using this method, GEM was measured in the range from 0.1 to 150 µM with a low limit of detection of 11.3 nM. In addition, the sensor showed high reproducibility, anti-interference ability and good stability for 6 weeks toward GEM detection. Finally, the proposed sensor exhibited excellent detection performance in complex pharmaceutical and biological matrices with satisfactory recoveries. •A molecular imprinting ratiometric electrochemical sensor is developed for the detection of gemcitabine.•The CuCo2O4/NCNTs nanocomposite is applied to amplify the signal.•The sensor exhibits excellent gemcitabine sensing performance in complex pharmaceutical and biological matrices.